Magic Realism and Shahnameh of Ferdowsi - Shamsayi, Mahin (Journal of History Culture and Art Research, 2017)
Magic realism, a concept that has been recognized in the world’s literary schools since the third decade of the twentieth century, still has a large number of advocates. It is read across the world with interest. Although the most prominent works of magic realism are those of Latin America, good examples of such work can also be found in other countries. Based on the new theory in the literary school, the first works appeared with the characteristics of magic realism are not the works of Latin American or European writers and have not been written in the present era, but is related to the world and oriental literature. In the ancient oriental myths and epics, such as One Thousand and One Nights stories and the epical and mythic Shahnameh of Ferdowsi one can also seek for traces of magic realism. The author of this research, after providing the definitions and attributes of magic realism has examined its origins in the Persian literature and Shahnameh of Ferdowsi and has remarked the most fundamental common points of these two styles which are indeed, the use of magic, legend and myth.